As imunidades parlamentares no Brasil após a Emenda Constitucional n. 35/2001 e a atual crise ética do Legislativo - Padula, Edgard (2007)
Legislative immunities were created to uphold the Legislative from pressures or threats, primarily by the Executive, as a means to provide more autonomy for the lawmakers to exercise their constitutional duties, such as debating and watching over the Administration which is the main reason for the governing system to be divided in three. For this reason we analyzed the most fail-safe doctrine addressing democracy, the General Theory of the State, the Legislative and political parties. We studied the theory of freedom from arrest and procedural immunity, as well as testimonial immunity and from incorporation to the Armed Forces, comparing the current system to the one in force prior to Constitutional Amendment 35/2001. We analyzed the institution at federal, state and municipal levels. We presented and analyzed the system of immunities in comparative law was submitted and analyzed vis-à-vis the laws of more relevant countries and those with greater proximity to Brazil, both in terms of geography as well as culture. We confronted countless laws, doctrine and case law. It is a fact that immunities were not conceived for the personal benefit of the legislative officers; however, corruption is not uncommon to the Legislative and the parties involved are not always punished accordingly. We measured how far immunities can lead to impunity. Amendment 35/2001 reduced the breadth of immunities, primarily of the procedural ones, which was successful in allowing the penal actions to continue against legislative officers. Hence, our investigation as to why corruption in the Legislative has not diminished. To answer this question, sociological study was made to try to grasp the reasons for Brazilians considerable lack of interest in politics and to understand politics twists and turns, despite my two decades of democratic experience. In the 2005/2006 biennium, various scandals of corruption were uncovered and repeatedly covered by the press, but did not result in very substantial sanctions. The average Brazilian citizen s behavior is far from civic, patriotic and gregarious. As a consequence, he/she does not closely watch over the lawmaking process, is not always concerned with strictly abiding by the laws or ensuring that others do the same, both in the public and private spheres. Citizens do not closely inspect the Parliament and the Administration as a whole. This detachment prevents citizens from understanding the nuances of politics and from pressing the government for results or behaviors, and consequently failing to demand punishment whenever it applies. In this scenario, we perceive that there is no Government for the people, and controlled by the people. Owing to considerable mismanagement of public moneys, the population is denied a more prosperous material life. It is noteworthy that legislative immunities are merely an aspect of many circumstances leading some politicians to show insignificant concern for ethics and legality, which defiles the image of the Legislative. The topic covered by this study stands out because it is current, relevant, complex and controversial, besides revealing a people who are needy of trustworthy and objective information, distant from parliament, and clearly inexperienced as to a citizen s duty.